Mobilizing Japanese youth the Cold War and the making of the sixties generation - Gerteis, Christopher, 1968- (Studies of the Weatherhead East Asian Institute, Columbia University., 2021)
"Examines the forces that shaped the political consciousness of Japanese youth who chose to engage in political violence during the 1960s and 1970s. The book argues in part that the intertwined political rhetoric of the far left and far right precipitated further levels of social alienation that helped to define the political consciousness of the 'Sixties Generation' well into the twenty-first century"--